PEMBENTUKAN IDENTITAS KELOMPOK DRUM CORPS SANG SURYA SMA MUHAMMADIYAH 1 PEKANBARU - Ma’ruf, Riyan Abdul; Asriwandari, Hesti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
Humans are creatures that naturally have the instinct to live with other humans. The desire of humans to want to be in groups is to maximize their own potential. One of them is by joining the organization. One such organization is the Marching band. Marching band or Drum Corps is a group or a line-up unit that plays music simultaneously and moves to form a choreo or visual. Many schools have made marching bands part of their extracurricular activities.SMA Muhammadiyah 1 is one of the high schools that has a marching band extracurricular called Drum Corps Sang Surya. The purpose of this research is to find out how the activities and activities of the Drum Corps Sang Surya (DCSS) SMA Muhammadiyah 1 Pekanbaru and how the process of forming the identity of Drum Corps Sang Surya (DCSS) members. This research is expected to be a means of transforming thought and increasing the writer's knowledge and contribution of information in thought that leads to the formation of identity.This research took place from February to March 2020, using a qualitative descriptive research method, namely explaining and interpreting the data collected through interviews. From the results of this study, it can be concluded that the formation of identity experienced by DCSS is a sense of responsibility. Not only obeying the existing rules as a member, in the body of DCSS there are also staff consisting of their respective duties which must be carried out properly for the smooth running of DCSS activities. In addition, this sense of responsibility was formed through a tough and intense disciplinary process which resulted in the sense of pride that DCSS members had as a result of the experiences they had experienced that could not be found anywhere else. Keywords: Marching band, DCSS, identity formation